Conversations with Iannis Xenakis - Varga, Bálint András (London Faber & Faber, 1996)
The music of the Greek-born composer, Iannis Xenakis, has been called brutal and violent. He first studied as an architect, but then turned to composition and put to musical use his knowledge of higher mathematics. In these conversations he talks about his life and music.